Biological functions and therapeutic potential of SRY related high mobility group box 5 in human cancer - Xue, Juan-di; Xiang, Wan-fang; Cai, Ming-qin; Lv, Xiao-yun (Frontiers in Oncology, 2024)
Cancer is a heavy human burden worldwide, with high morbidity and mortality.Identification of novel cancer diagnostic and prognostic biomarkers is important for developing cancer treatment strategies and reducing mortality. Transcription factors, including SRY associated high mobility group box (SOX) proteins, are thought to be involved in the regulation of specific biological processes. There is growing evidence that SOX transcription factors play an important role in cancer progression, including tumorigenesis, changes in the tumor microenvironment, and metastasis. SOX5 is a member of SOX Group D of Sox family. SOX5 is expressed in various tissues of human body and participates in various physiological and pathological processes and various cellular processes. However, the abnormal expression of SOX5 is associated with cancer of various systems, and the abnormal expression of SOX5 acts as a tumor promoter to promote cancer cell viability, proliferation, invasion, migration and EMT through multiple mechanisms. In addition, the expression pattern of SOX5 is closely related to cancer type, stage and adverse clinical outcome. Therefore, SOX5 is considered as a potential biomarker for cancer diagnosis and prognosis. In this review, the expression of SOX5 in various human cancers, the mechanism of action and potential clinical significance of SOX5 in tumor, and the therapeutic significance of Sox5 targeting in cancer were reviewed. In order to provide a new theoretical basis for cancer clinical molecular diagnosis, molecular targeted therapy and scientific research.